STUDI EKSPERIMEN VARIASI WAKTU ELEKTROPLATING Zn TERHADAP LAJU KOROSI PADA BAJA AISI 1045 - Ahmad Nur Lintang; Novi Laura Indrayani; Ahmad Maulana (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2018)
Research has been conducted on the analysis of corrosion rate of zinc electroplating on AISI1045 steel in a corrosive medium of 3.5% NaCl and 5% NaCl. The electroplating time variationused is 5 minutes, 10 minutes, and 15 minutes. Corrosion rate was carried out by soaking steelfor 174 hours in NaCl medium and calculated by weight loss method. The ideal time in the Znelectroplating process is 10 minutes in 3.5% NaCl solution with a weight reduction of 0.023grams and a corrosion rate of 1.670723071 mpy, while in the Zn electroplating process for 15minutes in a 5% NaCl solution the weight reduction is 0.033 grams and the corrosion rate is2,386747245 mpy. The test results on microstructure using a metallurgical microscope can beconcluded that AISI 1045 steel without electroplating is easily exposed to corrosion comparedto the Zn electroplating process.